Promosi Wisata Berbasis Kearifan Lokal Melalui Penggunaan Media Sosial Bagi Pelaku UMKM - Rettobjaan, Vitalia Fina Carla; Yudha, Anak Agung Ngurah Bagus Arista; Bendesa, I Komang Gde; Wirajaya, Made Karma Maha; Savitri, Ni Luh Putu Ayu; Agustina, Febyola (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2024)
Badung Regency is one of the districts that has quite a lot of tourist areas and also business activities ranging from hotels, trade to MSMEs. Currently, technology and information develop and spread rapidly. Many people, from parents to young people, have the opportunity to use digital media to promote tourism and MSME businesses. The aim of this activity is to increase people's ability to use digital media to promote tourism and improve their business by using social media. This activity was held at the Sangeh Village Perbekel Office, Badung Regency. This community service activity is aimed at the Krama Desa Adat, Yowana, and Pakis in Sangaeh Village, Badung Regency, which consists of 105 people. Counseling is provided through the method of activities carried out. The result is a society that is able to use social media well and wisely; they can use social media to show the various potentials of their traditional villages.Keywords: business; promotion; social media.